(untitled) (Fountain Journal of Natural and Applied Sciences, 2017)
Time Dependent Density Functional Theory (TD-DFT/B3LYP/6-31G*) calculations have been performed on the optimized structure of 2, 3-diphenylcyclopropenone (DPCP) in the UV region of the spectra; giving energies, oscillator strength, dipole moment, µ and polarizability, α in solvents of different polarities. The study was also extended to the number of transitions, frontier orbital energy gaps (ELUMO - EHOMO) analysis of this strained ring donor - acceptor (D-A) molecular system to calculate its ionization potential (I), electron affinity (EA) and global hardness (η) in the solvent of choice. This aids in understanding the relationship between the structure and properties of this molecule.TD-DFT/B3LYP/6-31G* calculation results, when compared with the reported experimental studies results of the solvatochromic shift properties of this molecule, showed ten excited singlet states for DPCP in the UV region. This indicates minimum overlap of the electronic transition bands computationally. The increased ΔELUMO-HOMO (4.09 - 4.31eV), I and ƞ, the lower dipole moments and polarizability values as solvent polarity increased, suggests high stability of this compound in polar solvents. The excess polarizabilities obtained for its singlet excited states show that the excited state of this compound is more polar than its ground state, and that, the molecule is chemically active.